Relationship between corticotherapy and increased cardiac risk in patients with rheumatoid arthritis (Brazilian Journal of Pharmaceutical Sciences, 2022)
Rheumatoid arthritis is an autoimmune inflammatory joint disease with global prevalence of 0.4% to 1.0%. Extra-articular manifestations increase its morbidity and severity, and cardiovascular diseases present the greatest risk. Therapeutic approaches have been used to treat rheumatoid arthritis, often involving the use of multiple classes of drugs with different mechanisms and forms of action. Corticosteroid therapy is widely used in this therapeutic combination; however, its use has been widely questioned because of its high toxicity and some negative effects, including the possibility of increased cardiovascular risk, depending on the dosage. Some studies have provided important insights into how glucocorticoids have an impact on cardiac complications in patients with rheumatoid arthritis. Most of these studies have concluded that exposure to these drugs at high or cumulative doses is associated with increased risk of death, as well as possibly being associated with the presence of a positive rheumatoid factor.